Multi‐Dimensional Taylor Network‐Based Adaptive Tracking Control for Nonlinear Time‐Delay Systems Subject to Asymmetric Input Saturation Under Prescribed Performance - Zhai, Lian‐Lian; Zhao, Wei; Zhou, Ya‐Feng; Han, Yu‐Qun (International journal of adaptive control and signal processing, 2025)
ABSTRACT The objective of this study is to develop a new control method for nonlinear time‐delay systems with input saturation and to achieve the prescribed performance control target by exploiting the excellent approximation performance of multidimensional Taylor networks (MTNs). The transformation method is used to transform the complex saturation model into a simple model with bounded error, simplifying the controller design process. The MTN is used to handle the nonlinear functions of the system, and an original adaptive control algorithm is constructed with the help of the backstepping method. The proposed control approach is feasible and can implement the tracking error signal that falls into the desired prescribed scope with all the signals in the control system being bounded. Finally, the efficiency of the proposed approach is demonstrated by presenting simulation results. The block diagram of the control design process.